Five Layers Aurivillius Phases Pb2-xBi4+xTi5-xMnxO18: Synthesis, Structure, Relaxor Ferroelectric and Magnetic Properties - Zulhadjri Zulhadjri; B. Prijamboedi; A. A. Nugroho; N. Mufti; Ismunandar Ismu (Journal of Mathematical and Fundamental Sciences, 2011)
Synthesis of five layers Aurivillius phases, Pb2-xBi4+xTi5-xMnxO18 (0 "žT x "žT 1) were carried out by molten salts method using eutectic mixture of Na2SO4/K2SO4 salts (1:1 molar ratio) as the flux. The samples were characterized by X-ray diffraction powder and refined by Le Bail technique. The refinement results revealed that the samples with composition x = 0, 0.2, 0.4, and 0.6 formed five layers Aurivillius with the space group B2cb; however, the samples with x = 0.4 and 0.6 contained impurity as BiMnO3 and the additional phase of four layers Aurivillius (PbBi4Ti4O15) was also observed for x = 0.6. The samples with x = 0.8 and 1 resulted in two phases: four layers Aurivillius and BiMnO3. The dielectric properties of the Pb2-xBi4+xTi5-xMnxO18 show broad peaks with the temperature of the maximum of the dielectric constant (Tm) at temperature of 295, 295, 304, and 343"žaC at a frequency of 2 MHz for x = 0, 0.2, 0.4, and 0.6, respectively. The Tm of these samples is shift to the left with decreasing frequency as indication of relaxor ferroelectric behavior. The samples with x = 0.8 and 1 show anomaly at 514"žaC and 551"žaC which correspond to the transition phase of four layers Aurivillius. Magnetic properties for all samples containing Mn are paramagnetic.